2023
DOI: 10.1038/s41598-023-28540-0
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the United Nations sustainable development goals from the inclusive wealth perspective

Abstract: The statement of sustainability in the sustainable development goals (SDGs) framework needs to be supplemented by a formal proof that intergenerational well-being also improves. This is the first study that aims to provide empirical evidence that links the progress of the SDGs and the changes in well-being, which are proxied by the SDG Index and the Inclusive Wealth (IW) Index, respectively. We propose an SDGs-wealth model which was analyzed using a machine learning method involving a balanced panel of 147 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…A total of 40 sub-indicator items have been adopted according to academic literature (e.g. [11,13,15,22,27,33,35]), international technical indices and reports (e.g. SDG Indicator Metadata 2022, the World Cities Report 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 40 sub-indicator items have been adopted according to academic literature (e.g. [11,13,15,22,27,33,35]), international technical indices and reports (e.g. SDG Indicator Metadata 2022, the World Cities Report 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Both the Scopus and Web of Science databases indicate that most research on urban sustainability focuses on the USA, China, and Western Europe, and that research on Middle Eastern countries is lacking. However, authors such as Andriamahefazafy et al [11]; Allen et al [12]; Kawakubo et al [13]; Alawneh et al [14]; Ugiawan et al [15], have confirmed the need for further research of SDGs in the context of Middle East countries. Therefore, this study attempts to remedy this research gap by focusing on Saudi Arabia, as it is the largest country in the Middle East region.…”
Section: Introductionmentioning
confidence: 99%
“…Though the SDGs are more integrated than the MDGs, questions remain over whether they go far enough. Some of those questions revolve around the goals themselves (Sugiawan et al 2023). Other questions pertain to how countries implement the SDGs (Nilsson et al 2017).…”
Section: The Environmental Dimensions Of the Sdgsmentioning
confidence: 99%
“…For instance, to expedite the advancement towards Target 7.1, underprivileged economies could potentially resort to more cost-effective energy sources, such as coal, to guarantee the accessibility and reasonable pricing of energy for all. Nevertheless, this strategy could prove detrimental to the realization of Target 7.2, which aims to enhance the worldwide proportion of renewable energy, as well as other environmental-related goals such as SDG-12 and SDG-13 (Sugiawan et al, 2023). It is, therefore, crucial to carefully evaluate the potential trade-offs between short-term gains and long-term sustainability while pursuing these targets.…”
Section: Empirical Strategy: Linking the Footprint Of Energy Consumpt...mentioning
confidence: 99%
“…The aforementioned findings suggest that the energy transition towards low-carbon energy sources is beneficial for accelerating the achievement of a sustainable energy system, as depicted by Goal 7 of the SDGs. Furthermore, in the framework of inclusive wealth (see, for instance, Managi & Kumar, 2018) for a detailed explanation of the notion of inclusive wealth), Sugiawan et al (2023) showed that progress in Goal 7 will positively influence wealth accumulation, which is a necessary condition for achieving long-term sustainability. Thus, investing in low-carbon energy sources will be beneficial, not only for providing greater access to affordable and clean energy for all but also for achieving long-term sustainability in the framework of inclusive wealth.…”
Section: Promoting Access To Affordable and Cleanmentioning
confidence: 99%

Renewable Energy: Policy and Strategy

Ristiyanto Adiputra,
Muhammad Iqbal Habib,
Erwandi
et al. 2023